Salt reduction in salted jellyfish (Lobonema smithii) using a mechanical washing machine - Charoenchokpanich, Wiriya; Rungsardthong, Vilai; Vatanyoopaisarn, Savitri; Thumthanaruk, Benjawan; Tamaki, Yasutomo (Science, Engineering and Health Studies, 2020)
Edible salted jellyfish sold in local markets need proper rehydration before cooking. Multiple washing steps with water is a common practice but time consuming and labor-intensive. In the industrial, use of a washing machine for desalination is an alternative approach. This research aimed to determine the effect of water wash cycles in a jellyfish washing machine on salt reduction of rehydrated jellyfish. Salted jellyfish with an irregular sheet were mechanically washed for 1, 2, and 3 cycles, each for 15 min and with new wash water. Results showed that changes in the percentage of rehydrated jellyfish calculated as washing yield (%) and salt content determined by three analysis methods (titration, atomic absorption spectroscopy, and X-ray fluorescence spectrometry) significantly decreased with increasing numbers of wash cycles. The salt reduction may be due to the agitation and dilution effect during wash cycles. However, extended wash cycles caused soft texture and generated broken pieces, resulting in a higher loss of desalted product. Therefore, the selected wash cycle of 2 times yielded acceptable flesh quality and remaining salt content (1.02%). Using a mechanical washing machine could be an appropriate procedure for jellyfish rehydration, saving time, and increasing productivity.